Research and methodological basis for ensuring the financial security of banks in Ukraine - Balatskyi, Ievgen; Andrieieva, Vita; Solodovnik, Olesia; Lypchanskyi, Volodymyr; Андрєєва, Віта Анатоліївна (LLC CPC Business Perspectives, 2018)
In an unstable financial and economic, political and social context, a number of Ukrainian banks demonstrate downtrends in their profitability, liquidity, and solvency rates. With that, the financial health and the growth vector of the whole banking sector of the country in the strategic perspective precisely depends on the quality of measures taken to ensure the financial security of a banking institution. The article analyzes the concept of financial security of a bank from the standpoint of protective, dynamic, resource-functional, competitive and systemic approaches. The authors substantiate that the financial security of the banking system as a whole and that of an individual bank is an integral part of the financial security of the country. In addition, three methodological approaches to assessing the financial security of the country’s banking sector are identified and described, namely instrumental, system and target-oriented and criterial ones. Based on theoretical and methodological analysis of scientific works and methodological approaches, a system of research and methodological support for the bank’s financial security is proposed. © The author(s) 2019
Keywords: assessment; bank; financial security; financial security of the bank; methodical approach; security